Performance of Brownian-Motion-Generated universal portfolios during covid-19 pandemic - Khor, Wei Sheng (2022)
The universal portfolio is a portfolio investment strategy which aims to maximize the return and it proves to achieve good return. The algorithm introduced by Cover requires memory in order